Perceived parental warmth attenuates the link between perceived parental rejection and rumination in Chinese early adolescents: two conditional moderation models - Meng, Fanfei; Cheng, Cuiping; Xie, Yuntian; Ying, Haihua; Cui, Xinling (Frontiers in Psychiatry, 2024)
Background Prior studies have explored the association between perceived parental rejection-warmth and adolescents’ rumination, but it is unclear whether the interaction between perceived parental rejection and warmth can predict adolescents’ rumination in a Chinese context and whether this interaction varies by children’s gender during the post-COVID-19 era. Objective This study aimed to address these issues in Chinese early adolescents from a family system perspective. Methods A total of 910 adolescents (Mage = 13.63, 48.50% female) from two middle schools in Chongqing and Changsha, China participated in the survey, answering measures for demographics, perceived parental rejection-warmth, and rumination. Results The results show that adolescents’ rumination was positively related to perceived paternal rejection (r = 0.326, p <.001) and maternal rejection (r = 0.343, p <.001), and negatively related to perceived paternal warmth (r = -.184, p <.001) and maternal warmth (r = -0.125, p <.001). Moreover, perceived maternal warmth significantly moderated the link between perceived paternal rejection and adolescents’ rumination (boot effect = -0.066, 95CI% = [-0.124, -0.010]), but this moderating effect is only presented in boys not in girls (boot effect = -0.063, 95CI% = [-0.015, 0.140]). However, perceived paternal warmth moderated the link between perceived maternal rejection and rumination in adolescents (boot effect = -0.052, 95CI% = [-0.103, -0.001]), and this interaction varied by adolescents’ gender (boot effect = 0.103, 95CI% = [0.029, 0.177]). Conclusions Perceived Parental rejection and parental warmth co-exist in the Chinese family system, and they exert an interactive effect on adolescents’ rumination depending on their gender. It implies that both parents should be more accepting, caring, considerate, and warm toward their daughters, and it is also in line with the tradition and status quo of parenting in Chinese families. These findings have implications for Chinese parental co-parenting practices in families with adolescents and adolescence mental health counseling work.